High Diversity and Low Coinfections of Pathogens in Ticks from Ruminants in Pakistan - Laila Jamil; Cheng Li; Yifei Wang; Jabran Jamil; Wenya Tian; Di Zhao; Shijing Shen; Yi Sun; Lin Zhao; Wuchun Cao (Microorganisms, 2025)
Emerging tick-borne infections pose growing public health threats, causing global disease burdens and economic losses. In this study, tick-borne pathogens were detected in ticks collected from ruminants in 19 sites of Khyber Pakhtunkhwa Province, Pakistan, between 2023 and 2024. A total of 989 ticks, belonging to five species, i.e., Hyalomma marginatum, Rhipicephalus microplus, Rhipicephalus sanguineus, Rhipicephalus haemaphysaloides, and Haemaphysalis bispinosa, were tested by specific PCR followed by Sanger sequencing. In total, fourteen pathogens including two Anaplasma species, three Ehrlichia species, three Rickettsia species, one Babesia species, and five Theileria species were identified, with an overall infection rate of 20.2% (95% CI: 17.7–22.7%). Phylogenetic analyses revealed two undefined Ehrlichia species: Candidatus Ehrlichia hyalommae was exclusively detected in Hy. marginatum ticks, while Candidatus Ehrlichia rhipicephalis was only found in R. microplus. Additionally, an undefined Rickettsia, provisionally named Candidatus Rickettsia pakistanensis, was identified, which is phylogenetically close to R. sibirica in North Asia and R. africae in Africa, suggesting its potential pathogenicity to humans. Although coinfections of two pathogens were observed, the coinfection rates were quite low. The findings revealed a significant diversity of tick-borne pathogens in Pakistani ticks, which may pose risks to livestock and humans.